Morphological Differentiation among Estuarine Catfishes of the Family Ariidae of the Matang Mangrove Ecosystem, Perak, Malaysia - H.R, Singh,; V.C, Chong,; Ismail M, Zakaria- (Malaysian Journal of Science, 2003)
Morphometric and meristic analysis indicates that the six species of the ariid catfishes of the genera Arius recorded from Sungai Selinsing of the Matang mangroves can be distinguished on the basis of their pre-dorsal length, inter-orbital width, number of gill rakers and head length. Arius sangor has the longest pre-dorsal length and the widest inter-orbital width while Arius truncatus has the lowest number of gill rakers. Arius maculatus is separated from all other ariids of the area in having the highest number of gill rakers while A. caelatus is a species with the longest dorsal spine. Discriminant analysis employed has shed valuable insights on these morphological differentiations.